2008
DOI: 10.1190/1.2959139
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow monitoring in oil fields using downhole measurements of electrokinetic potential

Abstract: Downhole measurements of electrokinetic potential are a promising new technology for hydrocarbon reservoir monitoring. Using a 3D finite-element model combining both multiphase flow and electrokinetic components, we investigated the behavior of electrokinetic (streaming) potential during oil production in a range of reservoir environments. We found that streaming-potential signals originate at fluid fronts and at geologic boundaries where fluid saturation changes. As water encroaches on an oil production well,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
83
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 51 publications
3
83
0
Order By: Relevance
“…However, as pointed out by Saunders et al (2008), considerable uncertainties remain, particularly relating to the nature of the streaming-potential coupling coefficient in the high salinity and temperature conditions typical of hydrocarbon reservoirs, and during multiphase flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as pointed out by Saunders et al (2008), considerable uncertainties remain, particularly relating to the nature of the streaming-potential coupling coefficient in the high salinity and temperature conditions typical of hydrocarbon reservoirs, and during multiphase flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical modeling work has suggested that measurements of streaming potential, acquired using electrodes permanently installed downhole, could be used to monitor water saturation changes in the vicinity of a well during oil or gas production (Saunders et al, 2006(Saunders et al, , 2008. The streaming potential is due to inflow of water to the reservoir as the hydrocarbons are extracted, either from an underlying aquifer or from water injection wells.…”
Section: Introductionmentioning
confidence: 99%
“…Streaming potential measurement applying electrodes permanently installed downhole has been a promising reservoir-monitoring technology [5,6]. Jaafar et al (2009) have measured the streaming potential coupling coefficient in sandstones saturated with higher brine salinity and reported the values of streaming potential coupling coefficient changed with respect to rock texture or mineralogy, injected and formation brine salinity [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, inferring a firm link between SP intensity and water flux is still difficult. Recent modeling has shown that SP observations could detect at distance the propagation of a water front in a reservoir (Saunders et al, 2008). We distinguish 1) The steady-state and passive observations which consist in measuring the electrical self-potential (SP).…”
Section: Introductionmentioning
confidence: 99%